ANALISIS KOMPARATIF PENDAPATAN USAHA BUDIDAYA IKAN LELE DAN IKAN MAS DI DESA TEGAL REJO KECAMATAN BELITANG I KABUPATEN OGAN KOMERING ULU TIMUR (JASEP, 2021)
Income Analysis of Catfish and Carp Cultivation in Tegal Rejo Village, Belitang I District, Ogan Komering Ulu Timur Regency. This research was carried out in Tegal Rejo Village, Belitang I District, Ogan Komering Ulu Timur Regency. The data collection method used in this study was observation and questionnaires as a data collection tool. Processing method and data analysis using t test analysis. The results of this study indicate that (1) the average income of catfish farming is Rp. 8,012,464 and the income of carp cultivation is Rp. 9,145,517 per season, (2) the largest fish farming income received by carp farmers is greater than the income of catfish farmers because the selling price of carp is more expensive. Keywords: aquaculture, fish, comparative, income, business